A COMPARATIVE LEGAL STUDY ON NEOBANK BETWEEN SOUTH KOREA AND INDONESIA - John Elvin Louis; Beumhoo Jang (Journal of Law and Policy Transformation, 2022)
Development of technology in the banking sector has introduced the concept of Neobank (digital bank or Internet-only bank) in South Korea and Indonesia. This study aims to analyze the regulations of in South Korea and Indonesia in order to ascertain the differences and similarities of the regulations of the two countries and eventually to provide the ideal regulatory solution in managing Neobank. The research adopted a comparative law research which is one of the types under normative legal research. It utilized secondary data. The primary legal materials were the Act on Special Cases Concerning Establishment and Operation of Internet-Only Banks of South Korea and the Indonesian Bank Circular No.6/18/DPNP 2004 and Regulation of Financial Services Authority No.12 /POJK.03/2018. The secondary legal materials consisted of articles journals, books and other materials relevant to the topic under discussions. All secondary data was collected from library research and it adopted an analytical and juridical qualitative approach. It found that the establishment of a Neobank in South Korea and Indonesia are both regulated in the banking laws of each country in general, but have their own specific regulations. South Korea is under the Act and Indonesia is at the regulatory level of the Financial Services Authority. Fundamentally, South Korea's Neobank is more progressive in implementing its technology than Indonesia, which still uses conventional bank (commercial banks) as the backbone to operate in the form of digital bank.